2020
DOI: 10.1002/jhbp.745
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor activity correlates with poor survival in patients resected for hepatocellular carcinoma

Abstract: Background/Purpose Few clinically useful biomarkers are known to predict prognosis in patients with hepatocellular carcinoma (HCC). The aim of this study was to investigate the correlation between PPAR activity and ALDH7A1 expression and their prognostic significance using RNA sequencing in patients undergoing liver resection for HCC. Methods We included patients undergoing liver resection for HCC at a tertiary referral center for hepato‐pancreato‐biliary surgery between May 2014 and January 2018. PPAR activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In spite of the active ingredients in acRoots for potential anticancer activity, this study further identified 11 key target genes, namely, AKT1, Casp3, EGFR, JUN, ESR1, Cat, PPARG, AR, HIF1A, RELA, and BCL2L1, by combining network pharmacology with WGCNA analysis. Notably, our results are consistent with findings reported in previous studies [35][36][37][38][39][40][41][42][43][44]. Furthermore, GO and KEGG pathway analyses were performed to further illustrate the potential anticancer biological functions and regulatory pathway of acRoots.…”
Section: Discussionsupporting
confidence: 90%
“…In spite of the active ingredients in acRoots for potential anticancer activity, this study further identified 11 key target genes, namely, AKT1, Casp3, EGFR, JUN, ESR1, Cat, PPARG, AR, HIF1A, RELA, and BCL2L1, by combining network pharmacology with WGCNA analysis. Notably, our results are consistent with findings reported in previous studies [35][36][37][38][39][40][41][42][43][44]. Furthermore, GO and KEGG pathway analyses were performed to further illustrate the potential anticancer biological functions and regulatory pathway of acRoots.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Busso-Lopes et al [ 35 ] found that low expression of ALDH7A1 in extracellular vesicles from metastatic lymph nodes is correlated with reduced survival in oral cancer patients. Other prognosis-related mechanisms, such as the activity of peroxisome proliferator-activated receptors and DNA methylation, have also been shown to be influenced by ALDH7A1 expression [ 36 38 ]. Thus, the influence of ALDH7A1 on prognosis should be evaluated for individual cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing was used to evaluate the expression of PPAR in 52 patients undergoing hepatectomy for HCC. The results showed that altered PPAR activity was associated with reduced OS 84 …”
Section: Ppars and Related Pathways As Prognostic Biomarkersmentioning
confidence: 96%